Difference of Cycle Threshold Value, Oxygen Saturation and D-dimer to COVID-19 Vaccination - Redhono Harioputro, Dhani; Dasa Ramadhan, Arsyi; Nurhayatun, Evi; Budi Susilo, Satrio; Agung Prabowo, Nurhasan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Many factors can affect the prognosis of COVID-19 patients, and Cycle Threshold value can be used to estimate the amount of virus in the body. Oxygen saturation and D-dimer are important components in determining the severity. This study aims to analyze the difference of CT value, oxygen saturation, D-dimer, and degree of severity on vaccination state. This study is the observational analytic study of patients admitted to the isolation ward of a referral hospital in Surakarta, Indonesia. The analysis covered assessing the normality of the data, the Kruskal-Wallis correlation test, and ANOVA to assess the differences between variables. A total of 154 patients with, 65.6% of them did not participate in the full vaccination program. The results of the analysis showed a significant difference between the D-dimer and the degree of severity with a p-value of < 0.05, while the CT value and oxygen saturation had no significant difference with the vaccination state. Vaccination showed a significant difference with D-dimer and the degree of severity of COVID-19 infection, so giving a complete vaccine can reduce the severity of COVID-19 patients, and we recommended to be able to complete the vaccine for the whole community.